2022
DOI: 10.51253/pafmj.v72i1.3912
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Blood Group A2 in Northern Pakistan

Abstract: Objective: To determine the prevalence of A1 and A2 subgroups of blood group A in healthy blood donors of northern Pakistan. Study Design: Cross sectional study. Place and Duration of Study: Armed Forces Institute of Transfusion, Rawalpindi Pakistan, from Sep to Dec 2017. Methodology: The blood samples of donors reported during the study period at Armed Forces Institute of Transfusion were collected. ABO typing was performed and those in group A and AB were further subtyped using anti-A1 lect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…This difference may be due to ethnicity and higher ratio of cousin marriages in those areas. 8 Previous studies done in India showed almost same results with 95.9% of A1 antigen (subgroup A1) and 4.1% had no detectable A1 antigen (subgroup A2) and among AB group individuals 80.8% had A1 antigen (subgroup A1B) and 67(19.2%) had no detectable A1 antigen (subgroup A2B). 12 , 13 Study done in South India also showed similar results.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…This difference may be due to ethnicity and higher ratio of cousin marriages in those areas. 8 Previous studies done in India showed almost same results with 95.9% of A1 antigen (subgroup A1) and 4.1% had no detectable A1 antigen (subgroup A2) and among AB group individuals 80.8% had A1 antigen (subgroup A1B) and 67(19.2%) had no detectable A1 antigen (subgroup A2B). 12 , 13 Study done in South India also showed similar results.…”
Section: Discussionmentioning
confidence: 54%
“…However, studies were done in Northern Pakistan recently with the same objective. 8 So, the present study will help to establish the prevalence of A2 subgroup in our region of the province Punjab, which will help to establish the need of A2 testing as a routine blood banking procedure.…”
Section: Introductionmentioning
confidence: 85%
“…A study conducted in northern Pakistan has documented similar results showing the frequency of Blood Groups A1 and A2 being 21.6% and 3.2%. 13 The prevalence of Blood Group A1 and A2 in Rayalaseema (India) is approximately 95.8% and 4.1% with anti-A1 lectin, respectively. 14 study from west India has described similar results showing the prevalence of A2 on anti-A1 typing to be around 3.0%.…”
Section: Discussionmentioning
confidence: 99%